Plasma modification of microporous polymer membranes for application in biomimetic dissolution studies - Michael M. Puppolo; Justin R. Hughey; Bruce Weber; Traciann Dillon; David Storey; Elizabeth Cerkez; Susan Jansen-Varnum (SpringerOpen, 2017)
Abstract Biorelevant dissolution is an indispensable tool utilized during formulation development and optimization for the prediction of in vivo bioavailability of pharmaceutical agents. Within that framework, membrane-permeation dissolution methodologies are widely used to model drug absorption. The current work evaluates polymer membrane surface modifications for production of biomimetic membranes to be employed in biorelevant dissolution studies. Biomimetic membranes exhibit hydrophilic and hydrophobic properties to simulate the intestinal membrane environment. Low temperature plasma treatment of microporous polyethersulfone (PES), nylon and polypropylene (PP) polymer membranes was applied to produce low energy surface layers with permanent hydrophobic and hydrophilic functionalities. Surface modifications on microporous polymer membranes were achieved by plasma treatments using tetrafluoromethane (CF4), perfluorohexane (C6F14), dichloromethane (DCM) and water (H2O). Surface characterization of treated membranes was evaluated using scanning electron microscopy energy dispersive x-ray spectroscopy (SEM-EDS), water contact angle (CA) and x-ray photoelectron spectroscopy (XPS) techniques. SEM-EDS analysis of polymer membranes treated with fluorinated and chlorinated solvents/gases depicts altered surface morphologies with enriched porosity. SEM-EDS and XPS analyses demonstrate the chemical modification at the surface of treated membranes is strongly influenced by the type of treatment gas or solvent. Results show fluorination as a more effective and less destructive treatment technique. XPS confirmed the presence of elemental fluorine functional groups at the surface of the PES and nylon membranes. Evaluating elemental changes (F/C ratio) from multiple techniques confirms fluorinated plasma treatments are localized to the surface of the membrane and do not significantly affect the bulk properties. In a supplemental study, a detailed comparison of the plasma treated polymer membranes and porcine intestines revealed the biomimetic nature of the modified membranes.